Determining the Purposes of Social Network Use of Students of Health Sciences, Their Opinions on the Use of Social Networks in Education, and Integrating Social Networks into Their Education - Emine Temizkan Sekizler; Burcu Karahasan; Gülten Sucu Dağ (Galenos Publishing House, 2021)
Objective:The objective of this study is to determine the purposes of social media use of students in the health sciences department, their opinions on the use of social networks in education, and integrating social networks into their education.Method:This is a descriptive cross-sectional study. The study population consisted of 1568 students in the Health Sciences Department of Eastern Mediterranean University. The study sample consisted of 309 students. Data were collected between February 2016 and March 2016.Results:The students were using social network sites the most for cooperation (13.47 ± 6.38) and the least for meeting people (3.63 ± 2.47). In the subdimensions of the Usage Purposes Scale of Social Networking Sites, statistically significant differences was found in meeting people based on gender (p = .010), meeting people based on age (p = .019), entertainment (p = .002), communication (p = .014). When asked about their opinion on integrating social networks into their education, 83.8% reported that social networks should be integrated into the education system.Conclusion:The study found that the students of health sciences use social network sites the most to meet people and the least to communicate. The study also found that the students expect social networks to help them share information-source and help them in group/team work and the students believe that integration of social networks into university education could be useful.